Perbandingan Penerapan Prinsip Transparansi Antara Indonesia dengan Irlandia dalam Hal Terjadinya Kegagalan Pelindungan Data Pribadi - Marsya Iffah Erisar Raib; Sinta Dewi Rosadi; Amelia Cahyadini (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2025)
The implementation of the principle of transparency in personal data protection is a crucial aspect in ensuring data subjects right to information relating to the processing of their data. Indonesia has enacted the Personal Data Protection Law (PDP Law) as a legal framework to protect citizens personal data. However, the implementation of the transparency principle in the PDP Law still faces various challenges, including the lack of notification data breach. This research aims to analyze the implementation of the principle of transparency in the event of personal data breach in Indonesia by taking the practice in Ireland as a benchmark for comparison. Ireland, as part of the European Union that adopted the General Data Protection Regulation (GDPR), has a higher level of a transparency and more rigorous enforcement mechanisms. In this research, the author uses a normative juridical method with a descriptive-analytical approach and collects data through literature study and semi-structured interviews. The results of this research show that although the PDP Law regulates the obligation regarding transparency in the event of a data breach, its implementation has proven to be ineffective due to the lack of awareness of data controllers and the absence of implementing regulations. This contrasts with Ireland, which has a better implementation as it is equipped with several supporting factors, including the existence of an independent authority. Therefore, it is necessary to strengthen regulations, establish independent supervisory institutions, and increase the awareness and compliance of data controllers to achieve a more optimum protection of personal data.